Analysis of the GPR17 receptor in NG2‐glia under physiological conditions unravels a new subset of oligodendrocyte progenitor cells with distinct functions. Issue 6 (23rd February 2023) - Miralles, Antonio J.; Unger, Nicole; Kannaiyan, Nirmal; Rossner, Moritz J.; Dimou, Leda
Abstract: NG2‐glia comprise a heterogeneous population of cycling cells that give rise to mature, myelinating oligodendrocytes. The mechanisms that regulate the process of differentiation from NG2‐glia into oligodendrocytes are still not fully understood but over the last years the G Protein‐coupled Receptor 17 (GPR17) has been on the spotlight as a possible key regulator. Interestingly, GPR17‐expressing NG2‐glia show under physiological conditions a slower and lower level of differentiation compared to NG2‐glia without GPR17. In contrast, after a CNS insult these react with proliferation and differentiation in a high rate, pointing towards a role in repair processes. However, the role of GPR17 + NG2‐glia under healthy conditions in adulthood has not been addressed yet. Therefore, we aimed here to characterize the GPR17‐expressing NG2‐glia. Using transgenic mouse models, we showed restricted GPR17 expression in only some NG2‐glia. Furthermore, we found that these cells constitute a distinct subset within the NG2‐glia population, which shows a different gene expression profile and behavior when compared to the total NG2‐glia population. Genetic depletion of GPR17 + cells showed that these are not contributing to the dynamic and continuous generation of new oligodendrocytes in the adult brain. Taken together, GPR17 + NG2‐glia seem to play a distinct role under physiological conditions that goes beyond their classic differentiation control, that needs to be further elucidated. These results open new avenues for using the GPR17 receptor as a target to change oligodendrogenesis under physiological and pathological conditions, highlighting the importance of further characterization of this protein for future pharmacological studies. Main Points: GPR17 + cells constitute a distinct NG2‐glia subset with a discrete gene expression profile. GPR17 + cells are not contributing to oligodendrogenesis in the adult, physiological brain. The GPR17‐protein is blocking differentiation in the adult brain.